2010
DOI: 10.1002/cjce.20387
|View full text |Cite
|
Sign up to set email alerts
|

Breakup of drops around the edges of Rushton turbine

Abstract: A detailed experimental and simulation study has been carried out in the present work to understand drop breakup in regions around the edge of the Rushton turbine in agitated vessels. The effect of impeller speed, impeller size, interfacial tension, and the viscosities of the two phases is studied on drop breakup through their effect on d max , the size of the largest drop in the system, and the whole size distribution. The measurements were carried out using Galai particle size analyser and optical microscope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Previous studies revealed that drop breakage is a function of different operating parameters such as the physical properties of dispersed and continuous phases, the tank's geometry, the power input, and the time of exposure to the turbulence field. [12] found that the d max is the same for both large and small impellers. Interfacial tension increases d max linearly [13], show that the d max for the pure breakup process decreases with time.…”
Section: Sauter Mean Diameter (D 32 ) and Maximum Diameter (D Max )mentioning
confidence: 85%
“…Previous studies revealed that drop breakage is a function of different operating parameters such as the physical properties of dispersed and continuous phases, the tank's geometry, the power input, and the time of exposure to the turbulence field. [12] found that the d max is the same for both large and small impellers. Interfacial tension increases d max linearly [13], show that the d max for the pure breakup process decreases with time.…”
Section: Sauter Mean Diameter (D 32 ) and Maximum Diameter (D Max )mentioning
confidence: 85%
“…Furthermore, it plays a key role to generate interfacial areas in order to determine the mass transfer rate between the phases in liquid-liquid systems [1][2][3]. Smaller drop sizes become more beneficial in mass transfer processes where they generate larger interfacial and mass transfer areas around the impeller area compared to drops with larger size [4,5]. The drop size distribution has consequences of the dynamic equilibrium between the drop break up and coalesce [6,7].…”
Section: Introductionmentioning
confidence: 99%